The Place of Kalenderism, a Wandering Turkish Dervish Tradition, in Islamic Thought - Erdoğan, İsmail; Polat, Esra (Çankırı Karatekin Üniversitesi, 2025)
Aim: This study aims to examine the origins of Kalenderism - a group of wandering dervishes-its place within Turkish-Islamic thought, its characteristics, and the fundamental ethical principles that distinguish it from other groups. Method: Using qualitative research methods, a literature review was conducted on the subject, and the information obtained from sources was classified by topic and analyzed. Results: Through an examination of various sources, this study identifies significant influences from ancient Turkish beliefs, Islam, Buddhism, as well as Indian and Persian cultures on the formation of Kalenderism. While known for their unconventional views and distinct appearance, attire, and lifestyle, this group is noted to follow a coherent life philosophy. This philosophy holds that material possessions are not an end but rather a means to live freely. Conclusion: Based on the information gathered, it is concluded that Kalenderism, while encompassing philosophical, mystical, and ethical principles, is a movement with a predominantly religious orientation that retains elements of ancient Turkish beliefs in various forms. Originality: This study can be considered unique in its approach by examining Kalenderism through the lenses of religion, history, philosophy, ethics, and mysticism, setting it apart from prior research on the topic.

Amaç: Bu çalışmada gezgin bir derviş grubu olan Kalenderîliğin doğuşu, Türk-İslam düşüncesindeki yeri, özellikleri ve kendilerini diğer yapılardan ayırt eden temel ahlak ilkelerinin tespit edilmesi amaçlanmaktadır. Yöntem: Çalışmada nitel araştırma yöntemleri kapsamında konuyla ilgili literatür taraması yapılmış ve kaynaklardan elde edilen bilgiler konularına göre tasnif edilerek bir değerlendirilmeye tabi tutulmuştur. Bulgular: Değişik kaynakların taranması suretiyle yapılan bu çalışmada, Kalenderîliğin teşekkülünde Eski Türk inançları, İslam dini, Budizm, Hint ve İran kültürü gibi farklı unsurların önemli ölçüde etkisinin olduğu tespit edilmiştir. İleri sürdükleri fikirler yanında ayrıca giyim, kuşam ve yaşayış olarak aykırılıklarıyla dikkat çeken bu grubun aslında kendi içinde tutarlı bir yaşam felsefesinin olduğu ifade edilebilir. Bu felsefenin ise maddî olan hiçbir şeyin amaç değil bilakis özgür yaşayabilmek için bir araç olduğunu söyleyebiliriz. Sonuç: Kaynaklardan elde ettiğimiz bilgilere göre Eski Türk inançlarını değişik isim ve şekillerde bünyesinde taşımakta olan Kalenderîliğin felsefi, tasavvufi ve ahlaki ilkelere sahip olmakla birlikte dini yönü daha ağır basan bir akım olduğu sonucuna varılmıştır. Özgünlük: Bu çalışma, daha önce yapılmış olan araştırmalardan farklı olarak Kalenderîliği din, tarih, felsefe, ahlak ve tasavvuf ekseninde ele alması bakımından özgün bir araştırma olarak görülebilir.
Gezgin Bir Türk Dervişliği Olan Kalenderîliğin İslam Düşüncesindeki Yeri
Keywords: Turkish and Islamic Intellectual History; Türk İslam Düşünce Tarihi